2019
DOI: 10.1038/s41408-019-0254-0
|View full text |Cite
|
Sign up to set email alerts
|

Gain of Chromosome 1q is associated with early progression in multiple myeloma patients treated with lenalidomide, bortezomib, and dexamethasone

Abstract: Gain of chromosome 1q (+1q) is commonly identified in multiple myeloma and has been associated with inferior outcomes. However, the prognostic implication of +1q has not been evaluated in the setting of standard triplet regimens. We retrospectively analyzed 201 consecutive patients with newly diagnosed myeloma who received induction with lenalidomide, bortezomib, and dexamethasone (RVD) and were tested for +1q at diagnosis by fluorescent in-situ hybridization. Patients with +1q (n = 94), compared to those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(163 citation statements)
references
References 28 publications
(34 reference statements)
10
147
1
1
Order By: Relevance
“…Gain(1q) is observed in ~40% of MM cases and in several other types of cancer, including breast cancer, hepatocellular carcinoma and myeloproliferative neoplasms, and has been the subject of numerous studies in the past decade [40][41][42][43] . A recent study has shown that newly diagnosed MM patients with gain of 1q who received induction therapy with bortezomib, lenalidomide and dexamethasone (VRD) are at higher risk of early relapse, especially when amp(1q) is detected 28 . Another study found that relapsed/refractory MM patients (RRMM) with gain of 1q have worse outcomes after treatment with Daratumumab 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gain(1q) is observed in ~40% of MM cases and in several other types of cancer, including breast cancer, hepatocellular carcinoma and myeloproliferative neoplasms, and has been the subject of numerous studies in the past decade [40][41][42][43] . A recent study has shown that newly diagnosed MM patients with gain of 1q who received induction therapy with bortezomib, lenalidomide and dexamethasone (VRD) are at higher risk of early relapse, especially when amp(1q) is detected 28 . Another study found that relapsed/refractory MM patients (RRMM) with gain of 1q have worse outcomes after treatment with Daratumumab 44 .…”
Section: Discussionmentioning
confidence: 99%
“…3A, 3B). Since the number of 1q copies has been previously reported as being prognostically relevant 28,29 , we evaluated it across all the subgroups. Sub-group 2e had the highest number of copies (p=0.0001) (Supp Fig.…”
Section: The Gain Of 1q Is the Most Significant Independent Determinamentioning
confidence: 99%
“…Nevertheless, another study published by Fonseca found that 1q21 gain lost its independent prognostic value in multivariate analysis, 16 which indicated that the adverse impact of 1q21 gain might be contributed to other high‐risk factors. As to the era of novel agents, although the response rate and survival of MM have been largely improved, most studies supported the conclusion that 1q21 gain was an adverse indicator in patients treated with novel agents and ASCT, 26,27 while some demonstrated that 1q21 gain lost its prognostic value in bortezomib‐treated patients 28 . A study of Asian patients analyzed the role of 1q21 gain in different treatment strategies, and found that the presence of 1q21 gain deterred PFS to bortezomib and lenalidomide, while ASCT was also less effective in patients with 1q21 gain 29 .…”
Section: Discussionmentioning
confidence: 99%
“…3C, 3D). Since the number of 1q copies has been previously reported as being prognostically relevant, we evaluated it across all the sub-groups 22,23 . Sub-group 2e had the highest number of copies (p=0.0001) (Supp Fig.…”
Section: Survival Analysis Of Mm-psn Reveals Novel Prognostic Findingmentioning
confidence: 99%